DOI: 10.3990/1.9789036546478
|View full text |Cite
|
Sign up to set email alerts
|

Innovating HRM for employee-driven innovation : a multilevel perspective

Abstract: Lastly, I want to thank Martijn. For your great support and love. You were always there to listen to my stories and when I needed to talk about my frustrations, and you helped to find solutions to every problem. You asked the right questions and put me on the right track again. You were also willing to read and comment on my texts and were genuinely interested in my research. We could share our experiences about being a PhD, although we also frequently saw that this meant something different in the US than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 237 publications
(612 reference statements)
0
5
0
Order By: Relevance
“…EDI emphasizes innovation as a process wherein ordinary employees are seen as the primary sources and drivers of innovation (Saari et al 2015;Lempiala and Yli-Kauhaluoma 2019;Holmquist and Johansson 2019;Kurz et al 2018). Because these employees are not required to be involved in innovation, EDI is therefore described as an extra role behavior (Renkema 2018;Buhl 2018). The argument for employee participation is based on the idea that these employees regularly face challenges through their work practices and are ideally positioned as a source of innovation (Wihlman et al 2014;Båckstrom and Lindberg 2018).…”
Section: Employee-driven Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…EDI emphasizes innovation as a process wherein ordinary employees are seen as the primary sources and drivers of innovation (Saari et al 2015;Lempiala and Yli-Kauhaluoma 2019;Holmquist and Johansson 2019;Kurz et al 2018). Because these employees are not required to be involved in innovation, EDI is therefore described as an extra role behavior (Renkema 2018;Buhl 2018). The argument for employee participation is based on the idea that these employees regularly face challenges through their work practices and are ideally positioned as a source of innovation (Wihlman et al 2014;Båckstrom and Lindberg 2018).…”
Section: Employee-driven Innovationmentioning
confidence: 99%
“…As such, new models of innovation have suggested more active and diverse roles for all employees within the organization. One of these models is expressed through the conceptual framework of employee-driven innovation (EDI), which embraces innovation activities that are initiated and driven by ordinary employees (Renkema 2018;Smith et al 2012;Båckstrom and Lindberg 2018). To drive innovation implies that employees participate in both the generation of creative ideas and their implementation (Smith et al 2012;Bäckström and Lindberg 2019).…”
Section: Introductionmentioning
confidence: 99%
“…EDI is based on the notion that innovation can originate from employees outside of the R&D department or strategic level (Deslee and Dahan, 2018; Echebiri, 2020). It is characterised as an extra-role behaviour (Renkema, 2018), and the cooperation between the leader and their subordinates in the process is important (Saari et al , 2015). EDI has been conceptualised to include the emergence and search for ideas, idea generation and idea development and implementation.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…R&D-focused innovation in most companies has relied on the assumption that innovation requires special skills and should be restricted to a small group in the organization that possess these skills (Harmaakorpi & Melkas, 2012). Today, this assumption is no longer tenable as previous studies have shown that all employees have the potential to contribute to innovation (Engen, 2016;Båckstrom & Lindberg, 2018;Renkema, 2018). Employee-Driven Innovation (EDI) is a construct that describes an innovation emanating from employees who are not overtly required to do so (Høyrup, 2010;Kesting & Ulhøi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it refers to new ideas that are initiated and driven by ordinary employees well beyond their regular duties (Wihlman et al, 2014;Xin, 2016;Holmquist & Johansson, 2019). On this basis, EDI is described as an extra role behaviour (Buhl, 2018;Renkema, 2018) that begins at the job task and worker level (Høyrup, 2012). What this suggests is that employees who get involved in EDI are merely acting on their own free will.…”
Section: Introductionmentioning
confidence: 99%